Pengaruh Gadget Terhadap Minat Belajar Bahasa Inggris Siswa Kelas 6 Sekolah Dasar Suralaya - Azzahra Dwi Damayani; Desty Endrawati Subroto; Faisila Khalda; Mutiara Erya; Chika Abelia Nafisa; Astri Indriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Study English to 6th grade students of Suralaya Primary School. Data collection uses questionnaires or questionnaires that are loaded with indicators of the influence of gadgets and learning interests. The sample in the study was 40 students, in class VI of Suralaya Primary School. The Research Method that researchers choose is Quantitative, with questionnaires to 40 students. From the results of the study, it was found that as many as 98% of students increased their interest in learning English and 2% of students remained. Gadgets have a positive impact for Suralaya's 6th grade students, including facilitating communication, serving as a means of entertainment, increasing comfort in learning, and expanding knowledge. To reduce the negative impact of using gadgets, parents need to have an understanding of them, provide instructions, give explanations, give advice to children, as well as limit the duration of use of the device by children.